2005
DOI: 10.1029/2004gl022182
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear wave interactions as a model for naturally enhanced ion acoustic lines in the ionosphere

Abstract: [1] Incoherent radar scatter from the ionosphere will, for equilibrium conditions, show two symmetric ion-acoustic lines, one for each direction of wave propagation. Many observations, from the EISCAT Svalbard Radar (ESR) for instance, demonstrate that the symmetry of this ion line can be broken. An enhanced, nonthermal, level of fluctuations, i.e., Naturally Enhanced Ion-Acoustic Lines (NEIALs) might be observed. Several models have been proposed for explaining these naturally enhanced lines. Here, we conside… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Those results rely on an entirely different computational model 60 based on the weak turbulence approximation. We have studied more localized density gradients in ion density, but these were of scale lengths too short to be relevant for those previous studies, 17,18 and no conclusive results can be presented. Finally, we emphasize that our results have applications beyond their relevance for the ionospheric observations and apply for electrostatic plasma waves generated by low density cold electron beams in collisionless plasmas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those results rely on an entirely different computational model 60 based on the weak turbulence approximation. We have studied more localized density gradients in ion density, but these were of scale lengths too short to be relevant for those previous studies, 17,18 and no conclusive results can be presented. Finally, we emphasize that our results have applications beyond their relevance for the ionospheric observations and apply for electrostatic plasma waves generated by low density cold electron beams in collisionless plasmas.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies 17,18 indicated that these effects could be important. Those results rely on an entirely different computational model 60 based on the weak turbulence approximation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several theories have emerged in order to explain the source of NEIALs, namely the electron-ion and ion-ion two-stream instabilities as well as nonlinear wave-wave interactions (via Langmuir decay). The enhanced ion-acoustic fluctuations due to parametric decay of Langmuir waves remains the most promising, at least for explaining some observed features (see Kontar and Pécseli, 2005, and references therein).…”
Section: Application and Discussionmentioning
confidence: 99%
“…It might be possible to find a low velocity electron beam which generates unstable waves for u < 4u Te , but the decay Langmuir wave (''daughter wave'') obtained from these will be strongly Landau damped, implying that the growth rate of the decay instability becomes negligible. Also, the effects connected with plasma inhomogeneity have been largely ignored, although a consistent treatment of the ionospheric plasma density gradient can bring new understanding of the observational results [Kontar and Pécseli, 2005].…”
Section: Introductionmentioning
confidence: 99%